Social Media Marketing (SMM) Impact on Hotel Business Development: Private Mini Hotel Experience - Balova, Suzana; Orlova, Inga; Konovalova, Elena; Repina, Margarita; Shichkin, Igor (Anais Brasileiros de Estudos Turísticos, 2022)
Today, social networks are becoming increasingly popular for the promotion of the hotel business. One of them is Instagram – a free service with which it is possible to save, edit, and publish photos, as well as distribute them on other social networks. The popularity of Instagram is growing every year. The purpose of the article is to evaluate the use of Instagram of the most mini-hotels in Moscow to promote their services in the hospitality market and determine the main problems of using Instagram to establish effective communication with customers. The article presents various approaches to the use of social media marketing (SMM) and discusses the features of the social network Instagram as one of SMM tools. Instagram accounts of mini-hotels in Moscow and the rating of mini-hotels in Moscow on Booking, Agoda websites were investigated in 2021, and the relationship between the content of Instagram accounts and the rating of mini-hotels in Moscow on the Booking and Agoda websites was analyzed. The results suggest that Instagram is a powerful SMM tool that allows effectively using and operating the versatile capabilities of a mini-hotel for successful organization and business, and the growing popularity of social networks contributes to the positioning of mini-hotel services through the Instagram network and becomes a reliable lever aimed at attracting the attention of potential customers.